Farcha Laboratory and rinderpest eradication programs in Chad from 1949 to 2007: a review - (:unkn) unknown (My University, 2021)
This work reviews the role of the Institut de recherche en élevage pour le développement (IRED), formerly Farcha Laboratory, in the control of rinderpest in Chad. Created in 1949 by colo-nial authorities, this laboratory located in N’Djamena has been playing a decisive role in rinderpest research in Central Africa since its creation. During the first period, or “Vaccines’ Period” (1953–1961), the laboratory’s work led to the production of several generations of vaccines. In the second period, or “Cam-paigns’ Period” (1962–1985), these vaccines were used on a large scale for disease eradication programs. The cell culture vaccines produced in Farcha were used in particular in the campaign launched by the Organization of African Unity (1962–1976) under the name of Joint Program No. 15. This program led to the temporary eradication of rinderpest in Chad. Unfortunately, the persistence of rinderpest outbreaks in several regions of Africa and the cessation of vaccination campaigns in Chad in the late 1970s led to its return in 1982. After relaunching vaccine production in 1983 and nationalizing the laboratory in 1985, Farcha kept playing a part in rinderpest control. During the third period, or “Surveillance Period” (1986–2007), the laboratory actively contributed to the Pan-African Rinderpest Campaign (PARC), then to the Pan-African Program for the Control of Epizootics (PACE), notably through epidemio-and sero-surveillance activities. These programs led to the definitive eradication of the disease in the region. Since 2007, Chad has been declared rinderpest-free, which has contributed to a rapid increase in the number of cattle in the country and has opened up trade opportunities, especially in the export of live cattle to neighboring countries.
Keywords: African Research